Gladys Black letter to Vernon M. Kleen regarding bird sightings, January 10, 1977 - Black, Gladyset al (1977)
Bird sightings were contributed by Gladys Black in a letter to Vernon M. Kleen. Her report on the Snowy Owls count includes a sighting map. The Red Rock Christmas count and the absence of Evening Grosbeaks are mentioned in the report. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1976-1977. Epson - sheet feed/flatbed